Decontamination of High-Efficiency Mask Filters From Respiratory Pathogens Including SARS-CoV-2 by Non-thermal Plasma - Obrová, Klára; Vaňková, Eva; Sláma, Michal; Hodek, Jan; Khun, Josef; Ulrychová, Lucie; Nogueira, Filomena; Laos, Triin; Sponseiler, Isabella; Kašparová, Petra; Machková, Anna; Weber, Jan; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
The current pandemic resulted in a rapidly increasing demand for personal protective equipment (PPE) initially leading to severe shortages of these items. Hence, during an unexpected and fast virus spread, the possibility of reusing highly efficient protective equipment could provide a viable solution for keeping both healthcare professionals and the general public equipped and protected. This requires an efficient decontamination technique that preserves functionality of the sensitive materials used for PPE production. Non-thermal plasma (NTP) is a decontamination technique with documented efficiency against select bacterial and fungal pathogens combined with low damage to exposed materials. We have investigated NTP for decontamination of high-efficiency P3 R filters from viral respiratory pathogens in comparison to other commonly used techniques. We show that NTP treatment completely inactivates SARS-CoV-2 and three other common human respiratory viruses including Influenza A, Rhinovirus and Adenovirus, revealing an efficiency comparable to 90 °C dry heat or UVC light. Unlike some of the tested techniques (e.g., autoclaving), NTP neither influenced the filtering efficiency nor the microstructure of the filter. We demonstrate that NTP is a powerful and economic technology for efficient decontamination of protective filters and other sensitive materials from different respiratory pathogens.